Solving topology optimization problems using nonmonotone spectral projected gradient method - Castillo Huamaní, Darwin (2021)
In this work, we propose the nonmonotone projected spectral gradient method to solve the problem of minimizing compliance of a static structure, classic problem in topology optimization. The present method has proof of global convergence and is easy to implement. The performance of the proposed method is studied through numerical examples in two dimensions.